Genetic variability and heritability of yield and yield components in some rice genotypes - A. Mohamed, Khalid; S. Ibrahim, Abu Elhassan; M. Mustafa, Ahmed (Gezira Journal of Agricultural Science, 2022)
Sixteen genotypes of rice ( Oryza sativa L.) were evaluated during 2008 and 2009 growing seasons at Ed-duim and Kosti to assess genetic variability and heritability of grain yield and its components in these locations. A randomized complete block design with three replicates was used in each location. The analysis of variance  mean squares revealed highly significant (P<0.01) differences for most of the studied traits in both seasons, indicating that these genotypes are highly variable. Genotypes differed significantly in grain yield. Genotypes NERICA 4 and NERICA 14 were the highest yielders (4.66 and 3.73 t/ha, respectively). Days to 50% maturity had the highest genotypic variance followed by number of grains per panicle and days to 50% flowering. The highest phenotypic variance was obtained by number of grains per panicle and days to 50% maturity. Broad sense heritability estimates varied among the studied traits. The highest heritability estimate (75%) was observed for days to 50% flowering, while the lowest (42.35%) was shown by grain yield. Days to 50% flowering and 1000 grain weight showed the highest heritability and hence could be used as selection criteria for grain yield improvement. The results suggested NERICA 14 and NERICA 4 as promising genotypes for further testing over locations and years.         اختبرت 16 سلالة من الأرز في الحقل في موسمي 2008 و2009 في الدويم وكوستى بهدف تقويم التباين ودرجة التوريث لانتاجية الحبوب ومكوناتها في بيئة هذه المواقع. استخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات في كل موقع. أظهرت نتائج تحليل التباين فروقات معنوية  (P<0.01) بين السلالات لمعظم الصفات التي درست. هذا يدل على وجود اختلافات وراثية كبيرة بين هذه السلالات. اختلفت السلالات معنويا في إنتاج الحبوب. كانNERICA 4 NERICA 14 أكثرها إنتاجية (4.66 و3.73 طن/هكتار على التوالي). اظهرت صفة عدد الايام حتى 50% نضج أعلى تباين وراثي تبعتها عدد البذور فى السنبلة وعدد الأيام حتى 50% ازهار. أعلى تباين مظهري ظهر في صفة عدد البذور في السنبلة ثم عدد الايام حتى 50%نضج. اختلف معامل التوريث على المدى العريض بين الصفات المدروسة. أعلى معامل توريث لوحظ لعدد الأيام حتى 50% أزهار (75%)، بينما أظهر إنتاج الحبوب درجة توريث متوسطة (42.35%) كذلك يمكن استخدام الصفات عدد الأيام حتى 50% نضج ووزن الالف حبة كمعايير للانتخاب لتحسين الانتاجية لانها اظهرت درجة توريث عالية. تقترح الدراسة الاصناف NERICA 4 و  NERICA 14كأصناف واعدة.